2010
DOI: 10.1111/j.1365-2036.2010.04506.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial DNA in the diagnosis of spontaneous bacterial peritonitis

Abstract: SUMMARY BackgroundDespite inoculation into blood culture bottles, ascitic fluid culture is negative in 50% of cases of spontaneous bacterial peritonitis (SBP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…Our 16S PCR was able to detect bacterial DNA in 100% (17/17) of culture-positive samples, and HRMA was able to correctly identify the bacterial species identified by culture in 70.6% (12/17) of positive samples in our study. The rate of positivity for bacterial DNA, 19.8% (21/106), detected from ascitic fluid samples in our study is comparable with the rates in other reported studies (3,4,8,9,11,12,(19)(20)(21)29). The overall sensitivity for detecting the presence of eubacterial DNA in an ascitic fluid sample and the specificity for the 16S PCR were high, at 100% (17/17) and 91.5% (85/89), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Our 16S PCR was able to detect bacterial DNA in 100% (17/17) of culture-positive samples, and HRMA was able to correctly identify the bacterial species identified by culture in 70.6% (12/17) of positive samples in our study. The rate of positivity for bacterial DNA, 19.8% (21/106), detected from ascitic fluid samples in our study is comparable with the rates in other reported studies (3,4,8,9,11,12,(19)(20)(21)29). The overall sensitivity for detecting the presence of eubacterial DNA in an ascitic fluid sample and the specificity for the 16S PCR were high, at 100% (17/17) and 91.5% (85/89), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Application of culture-independent PCR-based methods for the detection of bacterial DNA (bactDNA) in ascites has been proposed as a suitable tool to improve pathogen identification in patients at risk for SBP (6) and has indicated that bactDNA derives in most cases from a single pathogen (7)(8)(9). However, recent studies using 16S rRNA-based fingerprinting analyses have shown that ascites may also be polymicrobial (10,11) and that the bacterial spectrum is broader than that previously reported in context with SBP (11).…”
mentioning
confidence: 99%
“…15,16 Similar results were available for microbiological diagnosis in spontaneous bacterial peritonitis where RT-PCR increased the efficacy of cultures: RT-PCR detected pathogen in nearly all the patients with positive culture, and RT-PCR resulted positive in half of the patients with negative cultures. 17 Although molecular diagnosis cannot be considered as a replacement method in the clinical setting, there is an increasing awareness of the benefits, which may derive from the combined use of molecular analyses and conventional microbiology to optimize the research of pathogens. 16,24,25 Concerning our pilot study, RT-PCR has been undoubtedly a valuable tool to detect aggressive pathogens such as anaerobia, which are usually difficult to preserve alive in biological cultures.…”
Section: Articlementioning
confidence: 99%
“…[15][16][17][18][19] In pleural empyema, RT-PCR played an important role identifying pathogens in those patients with no culture growth, who had followed a previous antibiotic course. 15,16 Similar results were available for microbiological diagnosis in spontaneous bacterial peritonitis where RT-PCR increased the efficacy of cultures: RT-PCR detected pathogen in nearly all the patients with positive culture, and RT-PCR resulted positive in half of the patients with negative cultures.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation